Islamic sufi networks in the western Indian Ocean (c. 1880-1940): ripples of reform - Bang, Anne K. (Islam in Africa, 2014)
Preliminary Material -- 1 Introduction -- 2 The Luminescent Sun and Brilliant Rays of Light: Towards a Geography of Reform -- 3 The Branches of the Qādiriyya and the Shādhiliyya in Northern Mozambique: Silsilas to the South -- 4 The Shādhiliyya in Northern Madagascar c. 1890–1940: The Planting of a Garden and the Growing of Malagasy Roots -- 5 The Cape Town Muslim Community and East African Sufi Networks: Beyond the Monsoon -- Travelling Texts: Arabic Literate Learning in Coastal East Africa, c. 1860–1930 -- 7 Ritual of Reform – Reform of a Ritual: Rātib al-Ḥaddād in the Southwestern Indian Ocean, c. 1880–1940 -- 8 Consolidating the Network: Waqf Distribution and New Organizations in Zanzibar, c. 1900–1930 -- 9 Conclusions -- Appendix 1 -- Sources and Bibliography -- Index.